2012
DOI: 10.4161/auto.21561
|View full text |Cite
|
Sign up to set email alerts
|

Immune-related GTPase M (IRGM1) regulates neuronal autophagy in a mouse model of stroke

Abstract: Autophagy is an important cellular recycling mechanism through self-digestion in responses to cellular stress such as starvation. Studies have shown that autophagy is involved in maintaining the homeostasis of the neural system during stroke. However, molecular mechanisms underlying neuronal autophagy in ischemic stroke remain poorly understood. Previously, we and others have shown that immune-related GTPase M (IRGM; termed IRGM1 in the mouse nomenclature) can regulate the survival of immune cells through auto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 26 publications
1
42
0
Order By: Relevance
“…Indeed, accumulation of p62, which is an adaptor protein facilitating recruitment of ubiquitinated proteins to autophagosome via its interaction with LC3 and Gabarap family of proteins and is degraded during autophagic process [43], further argues in favor of autophagy downregulation after radiation exposure. Considering that Eif2ak3 and Irgm1 respectively are required for endoplasmic reticulum (ER) [44], and bacterial pathogen [45] mediated stress-induced autophagy activation, decreased expression of these factors will cause a faulty autophagic response to ER stress and immune challenges and increased vulnerability of intestinal cells to functional deregulation and pathologic infection. On the contrary, increased level of Snca [46] as well as ligand-mediated activation of Fas [47] is known to activate autophagy and downregulation of both the factors observed in our study further supports long-term downregulatory effects of sub-lethal radiation exposure on autophagy.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, accumulation of p62, which is an adaptor protein facilitating recruitment of ubiquitinated proteins to autophagosome via its interaction with LC3 and Gabarap family of proteins and is degraded during autophagic process [43], further argues in favor of autophagy downregulation after radiation exposure. Considering that Eif2ak3 and Irgm1 respectively are required for endoplasmic reticulum (ER) [44], and bacterial pathogen [45] mediated stress-induced autophagy activation, decreased expression of these factors will cause a faulty autophagic response to ER stress and immune challenges and increased vulnerability of intestinal cells to functional deregulation and pathologic infection. On the contrary, increased level of Snca [46] as well as ligand-mediated activation of Fas [47] is known to activate autophagy and downregulation of both the factors observed in our study further supports long-term downregulatory effects of sub-lethal radiation exposure on autophagy.…”
Section: Discussionmentioning
confidence: 99%
“…However, others have shown that autophagy can be neuroprotective by removing dysfunctional mitochondria [39]. Autophagic neuroprotection may also involve immune responses and other neuroprotective pathways [40]. Overall, the effect of autophagy in cerebral ischemia is likely complex with the extent and context of autophagy being key factor.…”
Section: Discussionmentioning
confidence: 99%
“…However in parallel with in vitro data, IRGM1 has recently been shown to induce autophagy in a mouse model of stroke. The promotion of autophagy, most likely at the level of LC3I to LC3II conversion, was generally protective [51].…”
Section: Fl/flmentioning
confidence: 98%